EAODV: A*-BASED ENHANCEMENT AD-HOC ON DEMAND VECTOR PROTOCOL TO PREVENT BLACK HOLE ATTACKS - Khalil I Ghathwan; Abdul Razak Yaakub; Rahmat Budiarto (Faculty of Computer Science - Universitas Indonesia, 2013)
Black hole attack is an attack where a node that responds to RREQ from the source node by replying a fake freshness information and false hop count. The black hole nodes do not respond to distributed co-operation in routing protocol to absorb all the packets, as a result, the network performance will drop. Most previous works are focused on anomaly detection through dynamic trusted of the neighbouring nodes. We find out that the internal comparisons take a long time. This loss can be shortened by changing the routing mechanism. We propose an enhancement of AODV protocol, named EAODV, that is able to prevent black hole attacks. The EAODV can find a shortest path of routing discovery using A* heuristic search algorithm. Values of hop count and estimate time to reach the destination node are used as input in the heuristic equation and one-way hash function is used to make a secure value and then to casting it to all neighbouring nodes. Experiments were conducted in NS2 to simulate EAODV in different running time with and without black hole nodes. The EAODV performance results are indicated better in terms Packet loss and Average End-to-End delay.